A Parametric Simplicial Formulation of Houthakker's Capacity Method - van de Panne, C.; Whinston, Andrew (Econometrica, 1966)
Abstract : The paper reformulates Houthakker's capacity method for quadratic programming in the framework of the Simplex and dual methods for quadratic programming, thereby greatly reducing the conceptual and computational complexities of the method. It is shown that the method is applicable for all convex quadratic programming problems, including the case of a semi-definite matrix of the quadratic form and that of constraints in equality form. The method reduces in the linear programming case to a parametric version of the dual method. (Author)